The Multisystem effects of Long COVID Syndrome and Potential Benefits of Massage Therapy in Long COVID Care - Wheibe, Elias; Dalkin, Benjamin; Meltzer, Haley C.; Russ-Sellers, Rebecca; Grier, Jennifer T. (International Journal of Therapeutic Massage & Bodywork, 2024)
Background: A major complication of infection with Severe Acute Respiratory Coronavirus 2 (SARS-CoV-2), the virus responsible for COVID-19, is the potential for Long COVID Syndrome. While the pathophysiology of Long COVID Syndrome has yet to be described, the disease presentation is characterized by long-term symptoms with debilitating effects on human health. A better understanding of Long COVID symptomology may open up new avenues for patient treatment such as massage therapy. Methods: From the PubMed database, cohort studies that examined post-infection COVID sequelae published between January 1st, 2021 and April 30th, 2021 were selected to investigate patient demographics and symptoms. A review of massage therapy literature since 2000 in conjunction with identified Long COVID symptoms was performed. Results: This systematic review identified 17 cohort studies across the world that investigated the symptomatology of patients suffering from post-COVID sequelae in multiple organ systems. We identified the pulmonary and nervous systems to be the organ systems most affected with post-COVID sequelae, with PTSD, fatigue, dyspnea, cough, sleep disturbances, loss of smell, abdominal pain, and decreased appetite as the most common symptoms reported by >20% of Long COVID patients. Massage therapy was historically found to provide benefits to patients experiencing similar symptoms to those identified in Long COVID. Conclusions: Recognizing the need for new approaches to treatment for Long COVID Syndrome, we identify massage therapy as a potential therapeutic treatment to positively impact the organ systems affected by Long COVID, especially the high-incident symptoms, and improve patient quality of life.